1997
DOI: 10.1063/1.473034
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of two-center integrals involving a rapidly oscillating free electron wave function

Abstract: Quantum Monte Carlo calculations of the dissociation energies of three-electron hemibonded radical cationic dimersOptical potentials are used in a quantum mechanical treatment of loss processes, e.g., ionization, where the loss of flux is described by the imaginary part. We present a numerical method for calculating two-center two-electron integrals necessary to construct the imaginary part of the optical potential. By introducing Slater-type orbitals with complex-valued exponents ͑CSTOs͒, we are able to repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The radial part of overlap integrals with the same screening parameters can be obtained by repeated application of recurrence relations (Eqs. 16,17,18,19,20,21,22,23) and an analytical formula (Eq. 2).…”
Section: The Calculation Methods Of the Case In Sect 23mentioning
confidence: 99%
See 2 more Smart Citations
“…The radial part of overlap integrals with the same screening parameters can be obtained by repeated application of recurrence relations (Eqs. 16,17,18,19,20,21,22,23) and an analytical formula (Eq. 2).…”
Section: The Calculation Methods Of the Case In Sect 23mentioning
confidence: 99%
“…STOs are still used in most semiempirical methods, usually as minimal valence sets, sometimes including d functions [15]. In ab initio theory, GTOs are now widely established, except for atomic ab initio calculations, which often employ STO bases [16,17,18] and some benchmark STO calculations on small molecules [19,20,21,22]. A comparison of STO and GTO bases needs about twice the size of a STO basis to obtain comparable accuracy [20,21]; thus, STOs bases are still very attractive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation 11 diers from the corresponding equation in the treatment of Zheng and Zerner [39] only in that it does need master formulae. Their one-centre results are special cases of Eq.…”
Section: One-centre Integralsmentioning
confidence: 99%
“…denote coordinate functions with respect to A. It has been shown that it is always possible to express a real spherical harmonic centred in P in terms of Cartesian monomials [11,39,40]:…”
Section: Preliminariesmentioning
confidence: 99%